PENGARUH TAX PLANNING TERHADAP MANAJEMEN LABA PADA PERUSAHAAN MANUFAKTUR SUB-SEKTOR MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA TAHUN 2019-2021 - Grace Purity Elisabeth Simbolon; Lorina Siregar Sudjiman (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
Profit is a form of management demand whose quality needs to be proven to show the company's development. However, if it turns out that there are unreported earnings, it cannot provide the actual situation where there may be opportunities to practice earnings management. To reveal earnings management, there are various strategies in it, including tax planning. The study was conducted by the author to examine the effect of tax planning on earnings management in companies listed on the Indonesia Stock Exchange in the food and beverage sub-sector for the 2019-2021 period. The sample used as many as 26 companies. The sampling technique used was purposive sampling. The type of data used was quantitative data with descriptive data analysis techniques, classical assumption test, multiple linear regression analysis, coefficient of determination, F test and T test using SPSS 26. Based on the results of the F test and T test, it was concluded that tax planning has a negative effect on earnings management and there is no simultaneous effect between variable X and variable Y.